Traditional Authority Of Tuan Guru Leadership In Integrating The Curriculum At The Darul Musthofa NW Islamic Boarding School - Safinah, Safinah; Ismail, Muhammad; Jayadi, Taupan (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Tuan Guru has position and power (authority) in Islamic boarding schools because Tuan Guru is an agent of change who brings change to Islamic boarding schools. Tuan Guru's power influences the education system in Islamic boarding schools. So integrating the madrasa curriculum with the Islamic boarding school curriculum is the policy of the authority of Tuan Guru. This research describes Tuan Guru's traditional authority in integrating the madrasa curriculum with the Islamic boarding school curriculum at the Darul Musthofa NW Islamic Boarding School. This research is descriptive qualitative research. Data collection by observation, In-depth interviews, and documentation. Data analysis by reducing data, presenting data, and clarifying data. The result; First, the traditional authority of Tuan Guru at the Darul Musthofa NW Islamic boarding school is demonstrated by (1) Islamic Boarding School feudalism by providing the closest family to take positions in the management structure of the Islamic Boarding School, (2) Wiridan Tradition such as wirid Hizib Nahdlatul Wathan and Thariqat Hizib Nahdlatul Wathan. secondly, the process of integrating the madrasa curriculum with Islamic boarding schools is based on four basic components in the madrasa curriculum, such as (1) Educational goals is to produce students who understand science, technology, and morals, (2) subject matter are based on the Turats books, (3) The methods used are classical-halaqah, mudzakarah method, memorization method, and Qiroati method, (4) The evaluation used is teacher evaluation and student evaluation Keywords: Traditional Authority, Tuan Guru, Integration Curriculum